2020
DOI: 10.1016/j.conbuildmat.2019.117259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water saturation on strength and deformability of building calcarenite stones: Correlations with their physical properties

Abstract: Stone construction elements are frequently in moist environments or in direct contact with water. Design and test standards have traditionally ignored the water impact on rock materials. However, several studies have shown that moisture can cause drastic strength reductions and deformability increase in some sedimentary rocks. For that reason, the main objectives of this work are: a) to quantify and understand the influence of water saturation on strength and deformability of four porous calcarenite building s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The greater values of σpeak, σres and Et obtained in R-1 in both conditions (dry and saturated states) may be explained by its lower porosity and higher density and P-wave velocity in comparison with R-2 and R-3, which exhibit similar mechanical behaviour and physical characteristics. In this sense, several authors have proposed increasing exponential or power correlation functions between physical properties (such as ρdry and vP) and mechanical properties (UCS and Et) as well as decreasing potential correlation functions between p and UCS (or Et) for sedimentary rock materials such as sandstones, travertines and calcarenites [20], [32], [54], [55]. The triaxial testing data of each building stone in dry and saturated conditions are summarized in Table 2.…”
Section: Triaxial Compression Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater values of σpeak, σres and Et obtained in R-1 in both conditions (dry and saturated states) may be explained by its lower porosity and higher density and P-wave velocity in comparison with R-2 and R-3, which exhibit similar mechanical behaviour and physical characteristics. In this sense, several authors have proposed increasing exponential or power correlation functions between physical properties (such as ρdry and vP) and mechanical properties (UCS and Et) as well as decreasing potential correlation functions between p and UCS (or Et) for sedimentary rock materials such as sandstones, travertines and calcarenites [20], [32], [54], [55]. The triaxial testing data of each building stone in dry and saturated conditions are summarized in Table 2.…”
Section: Triaxial Compression Testsmentioning
confidence: 99%
“…Specifically, in this work, three porous building stones with open porosities ranging from 10 to 18% and widely utilised in architectural constructions (monuments, emblematic buildings, stone masonry walls, building facades and decorative features) and civil engineering elements (bridge pillars, retaining systems, rockfills and foundations) were studied. Preliminary UCS tests carried out in quite similar materials showed that water saturation can cause significant reductions on their UCS when are saturated [32]. However, the influence of water under triaxial compression, which denotes a more genuine behaviour in specific situations, has not been studied in these building calcarenite stone varieties until now.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to the related research results in the field of rock mechanics [38][39], this study used exponential, logarithmic, and power functions to fit and analyze the relationship between the CPB strength and water saturation. The results are shown in Figure 6.…”
Section: Influence Of Water Saturation On Strengthmentioning
confidence: 99%
“…During the process of cryogenic fracturing, the use of LN 2 can produce a high thermal gradient and a rapid temperature change in the rock inner and outer body, leading to a greater thermal stress and more thermal cracks in HDRs compared with traditional water/air cooling [11]. Water was often used as a coolant in previous works, but water has the disadvantage that can even cause important reductions in the mechanical properties of nonheat-treated rocks [12,13]. Consequently, the physicomechanical properties of the HDR reservoirs are greatly influenced by LN 2 cooling treatments.…”
Section: Introductionmentioning
confidence: 99%